HUBUNGAN TANGGUNG JAWAB PENGINJILAN DAN KREATIVITAS BELAJAR FIRMAN TUHAN DENGAN KINERJA PELAYANAN - Frans Ansanay (Jurnal Dinamika Pendidikan, 2019)
ABSTRACT The purpose of this study was to determine the relationship of Evangelism Responsibility and Creativity in Learning Performance of servants with 50 samples selected. This study concludes that there is a significant influence and correlation between evangelism responsibility and ministry performance, creativity in studying the word of God with ministry performance and evangelism responsibility, creativity in learning the word of God together with ministry performance of God's servants. The research method was surveyed with correlational and regression analysis. The target population is STTIJA students in East Jakarta. For sampling techniques used Convenience or purposive sampling. The research instrument used by researchers and has been developed by researchers and the results: there is a positive and significant responsibility for evangelism with services with a regression formula: Y = 71,792 + 0.17 X1 significant at the 95% and 90% levels of trustees. There is a positive and significant correlation between the creativity of learning God's word with the performance of my ministry. The regression formula is Y = 78.965 + 0.109 X2. There is a positive and significant correlation of responsibility for evangelism and creativity to study God's word along with the ministry of performance of the ministers. The regression formula is Y = 60.757 + 0.169 X1 + 0.106 X2 at the 95% confidence level. Keywords: Evangelism and Creativity Responsibility, Service Performance ABSTRAK Tujuan dari penelitian ini adalah untuk mengetahui hubungan Tanggung Jawab Penginjilan dan Kreativitas Kinerja Pembelajaran pelayandengan 50 sampel yang dipilih. Penelitian ini menyimpulkan bahwa ada pengaruh dan korelasi yang signifikan antara tanggung jawab penginjilan dengan kinerja pelayanan, kreativitas mempelajari firman Allah dengan kinerja pelayanan dan tanggung jawab penginjilan, kreativitas mempelajari firman Allahbersamaan dengan kinerja pelayanan hamba Tuhan. Metode penelitian disurvei dengan analisis korelasional dan regresi. Sasaran populasinya mahasiswa STTIJA di Jakarta Timur. Untuk teknik pengambilan sampel digunakan Convenience atau purposive sampling. Instrumen penelitian yang digunakan oleh peneliti dan telah dikembangkan oleh peneliti dan hasilnya: ada tanggung jawab positif dan signifikan untuk penginjilan dengan pelayanan dengan rumus regresi: Y = 71.792 + 0,17 X1 signifikan di tingkat 95% dan 90% dari wali. Ada korelasi positif dan signifikan dari kreativitas pembelajaran firman Tuhan dengan kinerja pelayanan hamba. Regresi rumusnya adalah Y = 78,965 + 0,109 X2. Ada korelasi positif dan signifikan dari tanggung jawab untuk penginjilan dan kreativitas untuk belajar firman Allah bersamaan dengan pelayanan kinerja para pelayan. Formula regresi adalah Y = 60,757 + 0,169 X1 + 0,106 X2 pada tingkat kepercayaan 95%.. Kata kunci: Tanggung Jawab Penginjilan dan Kreativitas, Kinerja Pelayanan